The extracellular microenvironment in immune dysregulation and inflammation in retinal disorders - Biasella, Fabiola; Plössl, Karolina; Baird, Paul N.; Weber, Bernhard H. F. (Frontiers in Immunology, 2023)
Inherited retinal dystrophies (IRDs) as well as genetically complex retinal phenotypes represent a heterogenous group of ocular diseases, both on account of their phenotypic and also genotypic characteristics. Therefore, overlaps in clinical features often complicate or even impede their correct clinical diagnosis. Deciphering the molecular basis of retinal diseases has not only aided in disease classification but also helped in our understanding of how different molecular pathologies may share common pathomechanisms. In particular, these relate to dysregulation of two key processes that contribute to cellular integrity; namely extracellular matrix (ECM) homeostasis and inflammation. Pathological changes in the ECM of Bruch’s membrane have been described in both monogenic IRDs, such as Sorsby fundus dystrophy and Doyne honeycomb retinal dystrophy, as well as in the genetically complex age-related macular degeneration (AMD). Additionally, complement system dysfunction and distorted immune regulation may also represent a common connection between some IRDs and AMD. Through highlighting such overlaps in molecular pathology, this review aims to illuminate how inflammatory processes and ECM homeostasis are linked in the healthy retina and how their interplay may be disturbed in aging as well as in disease